Foetal aortic flow velocity waveforms in healthy and hypertensive pregnant women - Guedes-Martins, L; Cunha, A; Saraiva, J; Rita-Gaio, A; Cerdeira, A; Macedo, F; Almeida, H (BioMed Central, 2014)
Background: The foetal aortic Doppler frequency spectrum is influenced by cardiac output and contractility of the foetal heart as well as vascular compliance, blood viscosity and impedance of the arterial vascular system. The present study aimed at comparing Doppler flow pulsatility (PI) and resistance (RI) indexes of foetal proximal descending aorta (AoF) in the first, second and third trimesters of pregnancy, in low risk women and in those with chronic arterial hypertension, who had normal pregnancy outcomes. Methods: A longitudinal and prospective study was carried out in 101 singleton pregnancies (71 low-risk pregnancies and 30 with essential hypertension). Multivariate regression had to be considered due to the experiment’s nature: two different indexes were read on the same set of individuals, once at each trimester of the pregnancy [1st (11–14 weeks), 2nd (19–22 weeks) and 3rd (28–32 weeks) trimesters]. The response variable was denoted as index d, in a subject with hypertensive status h (hypertensive or normotensive), at continuous time t. Results: In both groups, AoF-PI and AoF-RI showed a small, but significant increase from the first to the second (1.850 ± 0.339 vs 2.110 ± 0.242 for PI, and 0.829 ± 0.068 vs 0.857 ± 0.038 for RI; p < 0.001) and the first to the third (1.850 ± 0.339 vs 2.163 ± 0.282 for PI, and 0.829 ± 0.068 vs 0.864 ± 0.037 for RI; p < 0.001) trimesters of pregnancy. The global model showed that while AoF-RI trends were converging as time progressed, the AoF-PI values exhibited a divergent trend (p < 0.05). Conclusions: Chronic stable hypertension in pregnancies with normal outcome, evidences an upward regular trend of foetal descending aorta pulsatility index that is similar to the normotensive condition.